Case report: Cerebrospinal fluid-derived circulating tumor DNA diagnoses and guides the treatment of a lung adenocarcinoma case with leptomeningeal metastasis - Bai, Yujun; Yu, Qingxi; Liu, Ning; Liu, Jingwen; Wang, Di; Liu, Xiaoli; Yuan, Shuanghu (Frontiers in Oncology, 2022)
Leptomeningeal metastasis (LM) occurs in 3~5% of non-small cell lung cancer (NSCLC) patients. Diagnosis of patients with LM and disease monitoring remains challenging due to the low sensitivity and specificity of the commonly used approaches, such as cerebrospinal fluid (CSF) cytology and magnetic resonance imaging (MRI). Therefore, new approaches are necessary to improve the detection of LM. Recent studies have shown that circulating tumor DNA (ctDNA) in CSF can be used to detect and monitor LM, but whether it can serve as an early diagnostic biomarker prior to cytological and radiographic evidence of LM involvement requires further evaluation. Here we report a lung adenocarcinoma patient who had detectable oncogenic mutations in the CSF ctDNA prior to confirmation of LM by CSF cytology and MRI, highlighting the potential application of CSF ctDNA in early detection of LM.